Formulation and Evaluation of Low Floating Lag Time Metformin Hydrochloride 500 mg Sustained Release Floating Tablet - Duy, Toan Pham (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Diabetes mellitus (DM) is a worldwide disease with high mortality rate. Metformin hydrochloride has been used as the first-line drug for the treatment of DM Type 2. However, the high water solubility and short half-life lessen the potential effectiveness of using conventional metformin tablet. Floating tablet is an attractive pharmaceutical formula which can make the drugs staying with an adequate time in the absorption part of the gastrointestinal tract (i.e., the stomach), and as a consequence, increase the oral bioavailability of drugs. Aim: To develop and evaluate novel metformin sustained release floating systems using combinations of polymers for the prolong release and absorption purposes. Materials and Methods: All of the ingredients used were qualified as pharmaceutical ingredients based on USP 36. The wet granulation and tableting method were used to formulate the systems. Quantitation method was developed and validated using ultraviolet (UV)-visible spectrophotometry method at the wavelength of 232.8 nm. Dissolution profile and in vitro equivalence test was done using paddle apparatus, 100 rpm/min, in 900 ml of phosphate buffer pH 1.2, at 37°C ± 0.5°C. Floating test was observed in simulated gastric condition. Physical tests (hardness, friability), weight uniformity, qualification, and quantification were performed followed USP 34 and BP 2013. Products’ kinetics profiles were also determined. Results and Discussion: We found that the combination of HPMC K15 and HPMC K100 with the ratio of 90:260 w/w, and the amount of NaHCO3 and citric acid at 65 mg and 13 mg, respectively, in the formulation could significantly lower the floating lag time to 1 min, and enhance the similarity value f2 to 79.78 compared to the reference drug Glucophage XR®. The systems’ kinetics followed the Higuchi model. Furthermore, the systems passed all analytical tests such as hardness, friability, weight uniformity, infrared qualification, and UV quantification. Conclusion: The combination of HPMC K15 and HPMC K100 can benefit the floating sustained release tablet formulation. These studies suggest that metformin may contribute for delivery system in the future.